Personnel protection and safety equipment for the oil and gas industries - Bahadori, Alireza (Waltham, MA : Gulf Professional Publishing is an imprint of Elsevier, 2015)
Oil and gas companies are repeatedly cited by regulatory organizations for poor training and maintenance on providing personal protective equipment to their refinery workers. Managers of refinery and petrochemical plants are responsible for instructing their workers with the types of equipment available, how to properly wear the equipment, how to properly care and maintain the equipment, and, most importantly, it's their responsibility to enforce these regulations and safety requirements. While there are many reference materials on the subject, most are too broad to apply directly to the uniq.
Front Cover; Personnel Protection and Safety Equipment for the Oil and Gas Industries; Copyright Page; Contents; Biography; Preface; Acknowledgments; 1 Breathing apparatus for personnel safety and protection; 1.1 Introduction; 1.1.1 Minimal acceptable program; 1.1.2 Medical limitations; 1.1.3 Communication; 1.1.4 Use of unapproved respiratory protective devices; 1.2 Selection of respiratory protective equipment; 1.3 Severity and location of the hazard; 1.3.1 Nature of the hazard; 1.3.2 Storage; 1.4 Special considerations; 1.4.1 Corrective lenses with full facepieces 1.4.2 Eyewear with half-mask facepiece1.5 Classification of respiratory protective equipment; 1.5.1 By purifying the air breathed; 1.5.2 By supplying air or oxygen from an uncontaminated source; 1.5.3 Self-contained breathing apparatus (SCBA); 1.5.4 Open-circuit escape BA; 1.5.5 Closed-circuit escape breathing apparatus; 1.6 Fresh-air hose and compressed air-line breathing apparatus; 1.6.1 General requirements; 1.6.2 Compressed-air-line apparatus (Demand-Valve Type); 1.6.3 Resistance to breathing; 1.6.4 Requirements for fresh-air hose apparatus 1.6.5 Requirements for compressed-air-line apparatus1.6.6 High-efficiency dust respirators; 1.7 Positive-pressure, powered dust respirators; 1.7.1 Design; 1.7.2 Power pack; 1.8 Respirators for protection against harmful dust and gas; 1.9 Dust respirators; 1.9.1 Design; 1.10 Gas respirators, canister type; 1.10.1 Design; 1.10.2 Canisters; 1.11 Gas respirators, cartridge type; 1.11.1 Design; 1.12 Positive-pressure, powered dust hoods and suits; 1.12.1 Design; 1.12.2 Hood and suit; 1.12.3 Power pack; 1.13 Underwater breathing apparatus; 1.13.1 Cylinders 1.13.2 Compressed air for human respiration1.14 Ventilatory resuscitators; 1.14.1 Classification; 1.14.2 Physical requirements; 1.14.3 Gas-Powered resuscitators; 1.14.4 Gas supply; 1.15 Nominal protection factor; 2 Masks and respiratory equipment materials; 2.1 Introduction; 2.2 Masks and respiratory equipment (Breathing apparatus); 2.2.1 Classification of respiratory equipment; 2.2.2 Classification of environment; 2.2.3 Classification of respiratory protective devices (see Figure 2.2); 2.2.4 Breathing apparatus; 2.3 Selection of breathing apparatus; 2.4 Respirators for dusts and gases 2.4.1 Filtering facepiece dust respirators2.4.2 High-efficiency dust respirators; 2.4.3 Positive-pressure dust respirators; 2.4.4 Filters; 2.4.5 Harness; 2.4.6 Connecting fittings; 2.4.7 Performance requirement; 2.4.8 Marking; 2.5 Positive-pressure, powered dust hood and suits; 2.5.1 Construction; 2.5.2 Hood and suits; 2.5.3 Power pack; 2.5.4 Performance requirement; 2.5.5 Marking; 2.5.6 Gas respirators, canister type; 2.6 Gas respirators, cartridge type; 2.6.1 Design and construction; 2.6.2 Tests and certification; 2.7 Combination respirators
Includes index.
Keywords: Petroleum industry and trade -- Safety measures